LABORATORY TEST EFFECT OF THE SLOPE ANGLE AND THE LOADING WITH PILE AS AN ALTERNATIVE TO SLIDING (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Increasing the pore water pressure effects the stability of the slope, this is caused by the soil shear strength depends on the presence of water in the soil itself. This experiment using the slope model test with the angle 45o, 60o, 70o  with load above slope and given pile reinforcement. Using the box of 40 cm x 160 cm, the height is 50 cm, slope model using clay. The space distance between the pile is 10D by using the configuration honeycomb. The main purpose of this experiment is to understand the behavior and to know the variable influence on the collapse of the slope. The variable observed are: knowing the relationship influence pore water pressure toward the safety factor, the relationship of the safety factor with the loading, and also the relationship of the safety factor with the time duration needed to collapse. Based on the results of data analysis testing that has been done, obtained the value of pore water pressure inversely proportional to the value of the safety factor and the value of the safety factor will be inversely proportional to the increase of loading. However, the value of these safety factors is directly proportional to the time of the collapse.